2007
DOI: 10.1186/1746-6148-3-20
|View full text |Cite
|
Sign up to set email alerts
|

Experimental transmission of atypical scrapie to sheep

Abstract: Background: Active surveillance for transmissible spongiform encephalopathies in small ruminants has been an EU regulatory requirement since 2002. A number of European countries have subsequently reported cases of atypical scrapie, similar to previously published cases from Norway, which have pathological and molecular features distinct from classical scrapie. Most cases have occurred singly in flocks, associated with genotypes considered to be more resistant to classical disease. Experimental transmissibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 22 publications
4
101
0
1
Order By: Relevance
“…So far, three distinct strains have been identified in the sheep and two of them stably passaged in the natural host: SSBP/1 (originating from the scrapie Cheviot sheep pool brain, [68]), CH1641 (isolated from a UK Cheviot sheep in the 1970s', [74]) and atypical scrapie [183].…”
Section: Strain Diversity In the Natural Hostmentioning
confidence: 99%
“…So far, three distinct strains have been identified in the sheep and two of them stably passaged in the natural host: SSBP/1 (originating from the scrapie Cheviot sheep pool brain, [68]), CH1641 (isolated from a UK Cheviot sheep in the 1970s', [74]) and atypical scrapie [183].…”
Section: Strain Diversity In the Natural Hostmentioning
confidence: 99%
“…In 2012 and 2013, it was found in *0.1 % of the w18 000 sheep which were tested in abattoir and fallenstock surveys each year (Ortiz-Pelaez & Arnold, 2013). Atypical scrapie is not thought to be naturally transmissible, although successful experimental transmissions have been achieved in sheep and transgenic mice; in the latter with similar pathology to that seen in the original sheep (Andréoletti et al, 2011;Le Dur et al, 2005;Simmons et al, 2007Simmons et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the placenta shed from goats with classical scrapie can transmit the disease to susceptible goat kids and lambs . Intracerebral transmissibility of the atypical/Nor98 agent has been demonstrated in rodent models (transgenic animals expressing the ovine PRNP), sheep and primate (Simmons et al, 2007 andGötte et al, 2011;Comoy et al, 2015). Experimental oral transmission of atypical scrapie showed that sheep carried AHQ/AHQ genotype developed the disease .…”
Section: Transmission Routes In Scrapiementioning
confidence: 99%